Growth of zinc oxide on pyrolytic graphite sheet by electrochemical and mist chemical vapor depositions. Issue 7 (7th April 2014) - Kake, Shunsuke; Uno, Kazuyuki; Furotani, Ikuhiro; Makabe, Harutaka; Yamasaki, Yuichiro; Tanaka, Ichiro
Abstract: Growth of zinc oxide (ZnO) on pyrolytic graphite sheet (PGS) by electrochemical deposition (ECD) and mist chemical vapor deposition (CVD) was investigated in the viewpoint of crystal orientations. We examined the fullwidth at half‐maximum (FWHM) of X‐ray rocking curve profiles of graphite 0002 and ZnO 0002 diffractions for the investigations. In the case of ECD, thermal annealing at 400, 800, and 1000 °C for PGS before the growth reduced the FWHM value of the grown ZnO. On the other hand, in the case of mist CVD, the growth process and an etching process which may flatten the surface roughness simultaneously occurred. As a result, the FWHM values of the grown ZnO and the PGS were almost the same. These results indicate that each ZnO grain was grown on each graphite grain along with a same c‐orientation direction. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)